Thermodynamic Properties and Characterizations of Chitosan Nano-Particles Corrosion Inhibition on The Surface of Mild Steelin Peat Water Media - Maria Erna; Emriadi Emriadi; Admin Alif; Syukri Arief (UNIVERSITAS SEBELAS MARET (UNS), 2016)
The thermodynamic properties and characterizations of corrosion inhibition of chitosan nano-particles on the surface of mild steel in peat water media had been studied using weight loss method at temperatures of 30 - 50 oC. Steel surfaces were characterized by FT-IR spectra and SEM-EDS morphology photos. The research found that the value of DGo approaching -40 kJmol-1. The negative value of Gibbs free energy shows that the adsorption of inhibitor molecules on the surface of mild steel was achemisorption and it occurred spontaneously. Meanwhile, the values of DHo is also negative confirming that the adsoprtion of inhibitor molecules is an exothermic process. The value of DSo obtained is positive, it indicates hat the inhibitor molecules were adsorbed spontaneously on the mild steel surface. The analysis on mild steel surfaces hows that the nano-particle chitosan was adsorbed on the steel surface to form the complex compounds.